IMPLEMENTATION OF BLENDED LEARNING IN OPTIMIZING THE ISLAMIC EDUCATION LEARNING PROCESS AT MUHAMMADIYAH IMOGIRI HIGH SCHOOL - Maghfirah Az-Zahra; Fani Rahmawati; Tyas Setyaningsih; Yona Fatmalla; Lovandri Dwanda Putra (Yayasan Amanah Nur Aman, 2026)
This study examines the application of blended learning in Islamic Education at Muhammadiyah Imogiri High School as a response to the transformation of learning in the digital age. Blended learning is understood as a learning strategy that combines the use of technology with the reinforcement of Islamic values. This study aims to analyze school policies and teacher readiness, patterns of blended learning implementation, as well as its impact and challenges on students' understanding of the material and the instillation of Islamic values. The study uses a descriptive qualitative approach with interview, observation, and documentation techniques. Data analysis was conducted using the Miles and Huberman model through reduction, data presentation, and conclusion drawing with source triangulation. The results showed that school policies and teacher readiness supported the adaptive implementation of blended learning in Islamic Education. Blended learning improved students understanding of the material and engagement, but still faced obstacles in terms of infrastructure and the depth of religious value internalization. This study concludes that blended learning is effective in Islamic Education learning if it is managed proportionally, supported by institutional policies, and balanced with face-to-face learning that emphasizes Islamic moral guidance.